THE CYTOPLASMIC FINE STRUCTURE OF THE DIATOM, NITZSCHIA PALEA - Drum, Ryan W. (The Rockefeller University Press, 1963)

(untitled)
The cytoplasmic fine structure of the motile, pennate diatom, Nitzschia palea was studied in thin sections viewed in the electron microscope. The cells were fixed in OsO(4), embedded in methacrylate, and immersed in 10 per cent hydrofluoric acid (HF) for 36 to 40 hours to remove the siliceous cell wall prior to sectioning. The HF treatment did not cause any obvious cytoplasmic damage. The dictyosome complex is perinuclear, and located only in the central cytoplasm. Mitochondria are sparse in the central cytoplasm, but abundant in the peripheral cytoplasm, and fill many of the transvacuolar cytoplasmic strands. Characteristic, amorphous oil bodies fill certain cytoplasmic strands and probably are not leucosin. The pyrenoid appears to be membrane limited, and oil droplets are found adjacent to the pyrenoid. The pyrenoid of another diatom, Cymbella affinis, is also membrane-limited. The membrane limiting the pyrenoid may be a composite of the terminal portions of chloroplast discs, facilitating rapid movement of photosynthate into the pyrenoid matrix, where the characteristic oil droplets may be formed. Carinal fibrils are found singly in each carinal pore, and may be involved in the locomotion of Nitzschia palea.